Similar values, different expectations: How do patients and providers view 'health' and perceive the healthcare experience?. (12th April 2022) - Natafgi, Nabil; Ladeji, Olayinka; Blackwell, Shanikque; Hong, Yoon Duk; Graham, Gail; Cort, Marcia; Mullins, C. Daniel
Abstract: Introduction: No one can argue on the importance of health in one's life. However, the value of health in the context of other priorities for individuals is not always as clear. Further, patients' experience with the healthcare system is rarely contrasted with the service providers' expectations. The aim of this paper is to examine and compare patients' and providers' own definitions of health and their perceptions of the healthcare delivery experience from the lens of residents and providers in West Baltimore, Maryland. Methods: This was a qualitative study with semi‐structured focus groups (15 sessions) and individual in‐depth interviews (21 interviews) with 94 participants. Two independent coders thematically analysed the transcripts. Results: Patients identified five areas where health systems can help them stay healthy or become healthier: affordability and costs of care; accessibility; clinician/patient communication; addressing social determinants; and stigma and trust. Providers acknowledged that the healthcare experience is not always perfect. While the medical team focuses on conversations that enhance medical care, patients are expecting providers to touch on subjects beyond medical care. Conclusions: Patients and providers need to consider that although they have a common value towards health, there is still a gap in what users expect and what providers can offer. To further align those expectations, there is a need for increasing involvement of patient in care administration and improving dialogue between the parties about these differences. Patient or Public Contribution: A Stakeholder Advisory Board (SAB)—comprised of a patient, two community leaders, a physician and two healthcare administrators—was instrumental in codeveloping the study material (e.g., interview guides), engaging patients in the research process, identifying participants and codeveloping dissemination material. Two SAB members—Gail Graham, a patient consultant/professor, and Marcia Cort, a physician—are coauthors.